First-Order Equations of Motion in the Supersymmetric Yang–Mills Theory with a Scalar Multiplet - Pavlyuk, A. M.; Yatsun, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We propose a system of first-order equations of motion all solutions of which are solutions of a system of second-order equations of motion for the supersymmetric Yang–Mills theory with a scalar multiplet. We find N = 1 transformations under which the systems of first- and second-order equations of motion are invariant.